2021
DOI: 10.1029/2021jb022103
|View full text |Cite
|
Sign up to set email alerts
|

A Newly Discovered Late‐Cretaceous East Asian Flat Slab Explains Its Unique Lithospheric Structure and Tectonics

Abstract: Different from normal subduction, flat slabs have small dip angles and lie nearly horizontally beneath an overriding plate. The best examples for ongoing flat subduction are those beneath South America, clearly seen in geophysical images (Gutscher et al., 2000;Hayes et al., 2012) and likely caused by subducting oceanic plateaus and nearby cratonic roots Manea et al., 2012). However, due to sparse observational constraints, the existence and mechanisms of flat slabs during the geological past remain debated, es… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
24
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 98 publications
4
24
0
Order By: Relevance
“…The linkage between the Izanagi plate subduction and the tectonic evolution of East Asia is still controversial because the slab dynamics of the Izanagi plate have not been well resolved. Previous studies have proposed flat-slab subduction of the Izanagi plate to be responsible for the East Asian lithospheric evolution in Mesozoic time Peng et al, 2021b). Our numerical results, which reveal multiple stagnation events of the Izanagi slab in Mesozoic time as an alternative mechanism, provide new insight into the Izanagi slab dynamics and its relation with the East Asian tectonics.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…The linkage between the Izanagi plate subduction and the tectonic evolution of East Asia is still controversial because the slab dynamics of the Izanagi plate have not been well resolved. Previous studies have proposed flat-slab subduction of the Izanagi plate to be responsible for the East Asian lithospheric evolution in Mesozoic time Peng et al, 2021b). Our numerical results, which reveal multiple stagnation events of the Izanagi slab in Mesozoic time as an alternative mechanism, provide new insight into the Izanagi slab dynamics and its relation with the East Asian tectonics.…”
Section: Discussionsupporting
confidence: 52%
“…The formation of such mantle wedge, which may lead to slab-triggered water release and vigorous mantle convective flow that could potentially weaken the lithosphere (e.g., Wang et al, 2016;Yang et al, 2017), is therefore supposed to be responsible for the Mesozoic evolution of the overriding plate that are characterized by magmatic activities and/or lithospheric instabilities in Eastern Asia (Ma and Xu, 2021). The intraplate magmatism along East Asia has disappeared in the Late Mesozoic (~80 Ma) and a flat slab model has been proposed to explain this magmatic termination (Peng et al, 2021b). In contrast, our numerical results still show a stagnation event at 90-70 Ma, but the resultant mantle wedge seems to be smaller than that in the middle Mesozoic (~130 Ma) which might be insufficient to cause large-scale magmatism.…”
Section: Discussionmentioning
confidence: 99%
“…In normal subduction circumstances, a steep slab subduction is a favorable situation for arc magma production (Peacock, 1990) and back‐arc extension (Sdrolias & Müller, 2006; Yang et al., 2018). Flat slab subduction is thought to greatly facilitate the transmission of compressive stress to the overriding plate (Lallemand et al., 2005; Liu et al., 2021; Peng et al., 2021), trench‐ward migration of the magmatic arc during the retreat of the flat slab (Wu, Yang, et al., 2019), and development of a prominent, syn‐flat slab magmatic lull (Henderson et al., 1984; Hu & Liu, 2016). Although previous studies have revealed the effect of slab dips on the tectono‐magmatic evolution in normal slab subduction, the effect may be opposite in the circumstances of mid‐ocean ridge subduction.…”
Section: Discussionmentioning
confidence: 99%
“…to trigger the reactivation of the NCC (Peng et al, 2021;Zheng et al, 2018;Zhu, Jiang et al, 2012). The thick (>180 km), cold and refractory lithosphere beneath the eastern NCC was replaced by thin (∼80 km) juvenile lithosphere (Menzies et al, 1993;Xu et al, 2004;Zheng et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…A significant effort is dedicated to deciphering the evolution of the NCC, especially its tectonothermal reactivation peaked in the late Mesozoic (Chen et al., 2008; Huang et al., 2009; Xu, 2001; Zheng et al., 2018). The destruction of the NCC is generally attributed to the westward subduction of the Paleo‐Pacific plate according to the first‐order spatial and temporal correspondence between these two events (Chen, 2010; Peng et al., 2021; Zheng et al., 2018). The predominant feature of the NCC is the E‐W contrast in the lithospheric structure, significantly thinning from west to east (Chen, 2010; Guo et al., 2016; Huang et al., 2009).…”
Section: Introductionmentioning
confidence: 99%